European economic and monetary union: Recent progress and possible implications for Latin America and the Caribbean - Rainer Schweickert; Roberto Zahler; Anneke Jessen (Inter-American Development Bank, 1997)
The theory and practice of economic integration have traditionally focussed on aspects of resource allocation. Except for the debate on optimal currency areas in the 1960s, which did not significantly influence regional integration efforts at the time, there has been relatively little analytical or empirical study of the monetary effects of integration. Recent developments in European integration have nevertheless placed such issues at the forefront of European policy debate. Particularly important in this respect is the European UnionZs aim to establish a single European currency, the Euro, by 1999 - one of the final and most decisive steps in its path towards economic and monetary union (EMU). Given its scope and influence on the regionZs internal environment, this project clearly represents a major historical and political leap in European integration. The principal aim of this report is to describe the process towards economic and monetary union in Europe, and by doing so, to offer Latin American and Caribbean policy-makers a broad overview of EMUZs main characteristics: its design, its key actors, its timetable and specific operating conditions.
Conference: Annual Meeting of the Boards of Governors of the Inter-American Development Bank (IDB) and the Inter-American Investment Corporation (IIC), Seminar 'Single currency of the European Union - Euro', March 18, 1997, Barcelona
Keywords: 330; Europäische Wirtschafts- und Währungsunion; EU-Staaten